2006
DOI: 10.1016/j.cell.2006.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Pot1 Deficiency Initiates DNA Damage Checkpoint Activation and Aberrant Homologous Recombination at Telomeres

Abstract: The terminal t-loop structure adopted by mammalian telomeres is thought to prevent telomeres from being recognized as double-stranded DNA breaks by sequestering the 3' single-stranded G-rich overhang from exposure to the DNA damage machinery. The POT1 (protection of telomeres) protein binds the single-stranded overhang and is required for both chromosomal end protection and telomere length regulation. The mouse genome contains two POT1 orthologs, Pot1a and Pot1b. Here we show that conditional deletion of Pot1a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
473
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 369 publications
(487 citation statements)
references
References 63 publications
11
473
1
2
Order By: Relevance
“…Depletion of endogenous TRF2 levels either by overexpression of dominant negative TRF2 (TRF2-DN) or through genetic knockout approaches in mouse cells with long telomeres results in massive chromosomal fusions with telomeric sequence at the sites of fusions. Mouse models in which shelterin components have been deleted experience telomere dysfunction, a DDR and chromosomal fusions resembling those observed in telomerase null mice 79,81,[84][85][86][87][88] . These results suggest that both critically short telomeres and direct disruption of the shelterin structure can initiate telomere dysfunction, trigger a DDR and chromosomal fusions.…”
Section: Box 1 the Shelterin Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of endogenous TRF2 levels either by overexpression of dominant negative TRF2 (TRF2-DN) or through genetic knockout approaches in mouse cells with long telomeres results in massive chromosomal fusions with telomeric sequence at the sites of fusions. Mouse models in which shelterin components have been deleted experience telomere dysfunction, a DDR and chromosomal fusions resembling those observed in telomerase null mice 79,81,[84][85][86][87][88] . These results suggest that both critically short telomeres and direct disruption of the shelterin structure can initiate telomere dysfunction, trigger a DDR and chromosomal fusions.…”
Section: Box 1 the Shelterin Complexmentioning
confidence: 99%
“…TRF1 is a negative regulator of telomere length while TRF2 plays important roles in preventing a DNA damage response (DDR) at telomeres. POT1 belongs to a family of evolutionarily conserved oligosaccharide/oligonucleotide-binding (OB)-fold containing proteins and specifically recognizes the single-stranded G-overhang [78][79][80][81] . Shelterin components that do not bind telomeric DNA directly include TIN2, which associates with TRF1 and TRF2 and TPP1, which forms a heterodimer with POT1 82,83 .…”
Section: Box 1 the Shelterin Complexmentioning
confidence: 99%
“…To examine this possibility, we monitored the status of the 3′ G-overhang in mSSB1 ∆/∆ MEFs and reconstituted cell lines using an in-gel hybridization assay [14,25]. The ratio of the ss G-overhang to total telomere did not differ appreciably in mSSB1 ∆/∆ MEFs expressing vector, mSSB1 WT , mSSB1 Y85A or mSSB1 F98A ( Figure 5D).…”
Section: Mssb1 and Mssb2 Protect Both Leading-and Laggingstrand Telommentioning
confidence: 99%
“…hPOT1 mainly regulates telomerase-mediated telomere extension (Colgin et al, 2003) and protect telomeres from end-to-end chromosomal fusions . In addition, hPOT1 may involved in cell cycle regulation (Wu et al, 2006), apoptosis (Wan et al, 2011) and so on. Many studies had reported that hPOT1 is correlated with a broad range of cancers, for example, gastric cancer (Wan et al, 2011), papillary thyroid cancer (Cantara et al, 2012), breast cancer (Shen et al, 2010), leukemia (Poncet et al, 2008).…”
Section: Expression Of Hpot1 In Hela Cells and The Probability Of Genmentioning
confidence: 99%